Calcifications in the infraspinatus muscle: An unusual complication of calcific tendinopathy - Zaid Ennasery, MD; Ismail Chaouche, PhD; Salma Abouchiba, MD; Amal Akammar, PhD; Nizar El Bouardi, PhD; Meriem Haloua, PhD; Moulay Youssef Alaoui Lamrani, PhD; Najia Hajjioui, PhD; Meryem Boubbou, PhD; Mustapha Maaroufi, PhD; Badreeddine Alami, PhD (Radiology Case Reports)
Calcific tendinopathy is a common disorder associated with the deposition of calcium hydroxyapatite crystals within tendons. The most prevalent location is the shoulder, where it affects the tendons of the rotator cuff. The calcific phase of this condition can be divided into formative, resting, and resorptive stages. During the resorptive stage, phagocytosis of the calcific deposits may occasionally result in their extrusion. These calcifications may migrate within the tendons or into adjacent tissues, leading to local inflammation and intense pain. Intramuscular migration of calcifications, as seen in this case, is particularly rare and poses significant diagnostic challenges. It is associated with increased pain and functional limitation compared to typical cases of calcific tendinopathy. Recognizing the imaging characteristics of these uncommon complications can help prevent the need for additional unnecessary investigations and facilitate prompt intervention. In this article, we present a case involving intramuscular migration of calcifications into the infraspinatus muscle, a rare complication of calcific tendinopathy. This case involves a 55-year-old patient who was dealing with persistent and debilitating shoulder pain.